KONTRIBUSI KEUNTUNGAN DAN UPAH TERHADAP NILAI TAMBAH INDUSTRI RUMAH BONGKAR PASANG (KNOCK DOWN) DI KABUPATEN OGAN KOMERING ILIR (STUDI KASUS : DESA TANJUNG BATU SEBERANG DAN DESA TANJUNG BARU PETAI) - Ismainy Ismainy (Jurnal Ekonomi Pembangunan, 2005)
This research takes title "the contribution profit and wages to value added of Knock Down industry in Ogan Komering Ilir Regency". The purpose of this research to analize how much contribution profit and wages of value added and correlation between its profit and wages. There were two village had been sample that were Tanjung Batu Seberang and Tanjung Baru Petai had been chosen into cluster sampling. In two village had done seventy six company, that could be used Slovin Formula. With used formula to calculate value added and contribution profit and wages, so resulted that contribution pofit of value added was 0,66 percent and contribution +wages of value added was 0,34 percent. It meant profit and wages were the biggest contibution inflience and also were the biggest contribution of value added. Connection with that, it also meant contribution of production factor very imprtant had created vslue added in knock down industry were enterpreneurÂ  skill and worker. Beside that, if contibution profit rised, so contribution wages would be decrease, and reverse. This fact correlation with trade off condition between had got profit with workers welfare whom could be meansured by wages level.Keywords: contribution , profit, value added, wages